The efficacy of DNA mixture to mixture matching. (July 2019) - Bright, Jo-Anne; Taylor, Duncan; Kerr, Zane; Buckleton, John; Kruijver, Maarten
Highlights: We investigate a method to identify a common contributor in two mixed DNA profiles. The discrimination power is limited by the smallest DNA contribution to the profiles. We show good ability to find pairs of profiles with a common contributor. This tool gives the ability to provide intelligence information. Abstract: Standard practice in forensic science is to compare a person of interest's (POI) reference DNA profile with an evidence DNA profile and calculate a likelihood ratio that considers propositions including and excluding the POI as a DNA donor. A method has recently been published that provides the ability to compare two evidence profiles (of any number of contributors and of any level of resolution) comparing propositions that consider the profiles either have a common contributor, or do not have any common contributors. Using this method, forensic analysts can provide intelligence to law enforcement by linking crime scenes when no suspects may be available. The method could also be used as a quality assurance measure to identify potential sample to sample contamination. In this work we analyse a number of constructed mixtures, ranging from two to five contributors, and with known numbers of common contributors, in order to investigate the performance of using likelihood ratios for mixture to mixture comparisons. Our findings demonstrate the ability to identify common donors in DNA mixtures with the power of discrimination depending largely on the least informative mixture of the pair being considered. The ability to match mixtures to mixtures may provide intelligence information to investigators by identifying possible links between cases which otherwise may not have been considered connected.